Effect of an organoclay on the reaction-induced phase-separation in a dynamically asymmetric epoxy/PCL system - J. Rotrekl; A. Sikora; L. Kapralkova; I. Kelnar; J. Dybal (eXPRESS Polymer Letters)
The addition of layered silicates can significantly affect the phase behaviour of both immiscible thermoplastic blends and partially miscible thermoset systems that undergo reaction-induced phase separation (RIPS) during curing. This study focuses on the phase behaviour of polycaprolactone (PCL)/epoxy in the presence of organically modified montmorillonite (oMMT). Due to the high dynamic asymmetry caused by the differences in the molecular weights and viscosities of the PCL and the uncured epoxy, the critical point is localised at low PCL concentrations, as indicated by the pseudophase diagram. The addition of oMMT to the system led to the marked shift of the critical point towards higher concentrations of PCL, with an increase in the oMMT content occurring as a consequence of the preferential localisation of the clay in the epoxy phase, making this phase more dynamically slow. Significant changes in morphology, including phase inversion of the PCL/epoxy systems caused by the presence of oMMT, were recorded for PCL concentrations ranging from 10 to 30%.